Razvoj mladja na izbranih površinah vetrolomov iz let 2008 in 2017 ter gozdnogojitvene smernice za obnovo - Fidej, Gal (Gozdarski vestnik, 2021)
In this paper, we analysed and compared regeneration after the 2008 and 2017 windthrow events. We found that the densities of natural regeneration between and within research sites were very diverse due to different ecological conditions during and after disturbance. Initial densities after three (windthrow 2017) or four years after the disturbance ranged from about 2,100 to 23,000 individuals per ha. Concerning species composition, spruce and beech were dominant among the late-successional species, while there was a considerable representation of pioneer and light-demanding species, such as willow, rowan, and birch, which made an important contribution to early successional forest recovery. The results of the research are supplemented with silvicultural guidelines for forest restoration. During post-disturbance salvage logging, attention is needed not to damage the existing advanced regeneration, which plays a major role in forest restoration. Natural regeneration should predominate, while artificial regeneration should be used on sites where we expect little or no natural regeneration. When using artificial restoration, following examples from abroad, silver fir and oak should be used more often. Weedings should be focused and not superficially employed over the entire artificially restored area, as it removes natural regeneration. Planting performance assessment must be introduced in the restoration system.
Keywords: forest restoration; gojenje gozdov; gozdnogojitvene smernice; naravna obnova; naravno pomlajevanje; natural regeneration; natural restoration; obnova gozdov; silvicultural guidelines; silviculture; ujme; vetrolomi; windthrows